Backstage at an animated series - Fingeroth, Danny (New York Children's Press, 2003)
Explores how animation works, how animated films are produced and who is best known for making them, and how to pursue one's interest in the field, either as a career or as a hobby
Historic movements -- Shaping the world of animation -- Movers and shakers -- A career come to life!
American Corner
Includes bibliographical references (p. 44) and index
11
Keywords: Animation (Cinematography) -- Juvenile literature; Animation (Cinematography)